Effect of Orphenadrine citrate drug on Corrosion of Stainless Steel (316L) in an Acidic Environment (Hydrochloric Acid) - Jassim, Rasha A.; Kadhim, Nafeesa J.; Mohammed, Halah J.; Farhan, Ahlam M. (Iraqi Journal of Science, 2022)
The use of varied quantities of orphenadrine to protect stainless steel against corrosion in an acidic media at 298 K has been investigated. It was observed that when the drug's concentration is increased, the drug's speed of corrosion lowers. The data of inhibition efficiency (percent IE) in the presence of orphenadrine drug and corrosion resistance showed that the highest protection efficiency was achieved with the best concentration, and that the corrosion rate decreased with increasing orphenadrine drug concentrations, making it a good inhibitor for stainless steel in an acidic environment. The theoretical investigation proved the efficiency of the drug for inhibition, as the drug is absorbed on the surface of the stainless steel by the active groups in the drug, using the hyperchem-8.07 software to compute the molecular orbital energies.